Urgensi Aktifitas Bermain di Era Game Online untuk Kebugaran Jasmani Anak - Sumaryanti Sumaryanti; Sumaryanto Sumaryanto; Wawan Sundawan Suherman; Yustinus Sukarmin; Wara Kushartanti; Ahmad Nasrullah; Setyawan Widyarto; Andi Sultan Brilin Susandi Eka Wahyudhi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
The purpose of this writing work is for children to develop gross and fine motor skills, strengthen muscles and bones, improve balance, coordination, and flexibility of the body. In addition, playing can also increase heart and lung strength, and help boost a child's immune system. Play activities also provide important social experiences for children. Through play, children can learn to interact with others, share and work together in teams. This can help improve a child's social and emotional skills. In addition, play activities can also help reduce the risk of obesity in children. This writing method uses a review study method about the fitness condition of children during the online game period. Data analysis in this study used several literature reviews which were then analyzed qualitatively. The conclusion of this writing is that in the increasingly advanced technological era, children tend to spend more time in front of gadget screens and move less. By playing, children can reduce their screen time and increase physical activity. Overall, play activity is very important for the physical fitness and health of children. Parents and caregivers must provide opportunities and support for their children to play and move actively. Keywords: Children's Fitness, Play Activities, Physical Fitness